Is production in global value chains (GVCs) sustainable? A review of the empirical evidence on social and environmental sustainabilitiy in GVCs - Michele Delera (Kiel Institute for the World Economy (IfW), Poverty Reduction, Equity and Growth Network (PEGNet), 2021)
Sustainability in global value chains (GVCs) hinges on the interplay between specialisation, scale, and efficiency effects. This paper reviews different strands of literature which provide evidence on these channels. The evidence that I collect suggests that the sustainability impacts of GVCs are ambiguous. By allowing firms to specialise through the offshoring of relatively more polluting production activities, GVCs are associated to sizeable amounts of carbon leakage. Insofar as firms expand following entry in foreign markets, environmental impacts may also increase. Yet at the same time, participation in GVCs makes firms more energy and emission efficient than their domestic peers through a variety of mechanisms. Thus, GVCs also contribute to dampen emission growth. In terms of social sustainability, GVCs are associated with an income premium for workers and producers alike, although these benefits are not equally distributed.
Keywords: 330